EFEKTIVITAS PENGGERUSAN BIJIH TIMAH PRIMER MENGGUNAKAN BALL MILL DI PT MENARA CIPTA MULIA DESA SENYUBUK KABUPATEN BELITUNG TIMUR - Eko Prayitno; E.P.S.B Taman Tono; Alfitri Rosita (MINERAL, 2018)
PT Menara Cipta Mulia is a primary tin mining company. The primary tin ore processing process includes comminution, sizing and concentration activities. The stage of primary tin ore comminution begins with the crushing process using a jaw crusher and then refined using a ball mill again. Ball mill is a form that is used to shrink the grain size of materials to obtain finer materials (fine materials) and preparation of the right size for the concentration process, namely size 60.degree. -200 mesh. Variable ball mill settings that are not appropriate welcome coarse ball mill scouring material (20 s.d. 50 mesh), so we need to do the grinding again because the minerals have not been taken from the impurity minerals. The ineffective process of grinding primary tin ore records high production costs. The experiment was carried out with bait stimulating variables 3-4 TPH, 4-5TPH, and 5-6 TPH. The bait size is 0-2 cm, 0-4 cm and 0-6 cm. The air rate is 4.436 l/h, 7.394 l/h, and 11.091 l/h. The experiment was conducted 27 times with the combined formula for the results of scouring the ball mill. Based on the experiments carried out, the right material for the process of concentration size 60 s.d. Was obtained. -200 mesh, because the size of the mineral has been released from the impurity minerals. The smaller feed bait, bait size, and air flow obtained from the materials resulting from the grinding of ball mill 60 mesh up to -200 mesh height. Effectiveness of grinding get in sample 19 with the highest production value of 5 s.d. 6 TPH. This parameter is used to get the right results for the concentration process, which is 60 mesh size. -200 mesh. The effective value of the feed rate variable 5 d. 6 TPH, feedback size 0-2 cm, and water rate 4.336 l/h.